Legacies, Transitions, and Advancing Normal Birth - Budin, Wendy C. (2007)
In this column, the new editor of The Journal of Perinatal Education discusses the significance of legacies, transitions, and advancing normal birth. The editor pays tribute to the legacies left behind by former editors Francine Nichols and Sharron Humenick and shares her vision for The Journal of Perinatal Education as it transitions into the next phase of advancing normal birth. The editor also describes the contents of this issue, which offer a broad range of resources, research, and inspiration for childbirth educators in their efforts to promote normal birth.